The investigations of thermal water structure by many-hours sounding data in the Antarctic stations regions - A. Yu. Artamonov; I. A. Repina; Yu. V. Artamonov (Ukrainian Antarctic Journal, 2010)
In the work the results of thermal water structure investigations at many-hours hydrological stations, carrying out R/V “Academic Fedorov” in 2009-2010 are presented. Shown, that the intradaily variability of temperature field is observed against a background of inter-daily changes, which due to displacement of boundary between cold shelf water and more warm ocean water. The water structure reconstruction is result from the active synoptic processes in atmosphere above Antarctic adjacent oceans areas.